Examining the influence of communication technology, image technicalities, and image narrative on environmental awareness in the digital age: a study of worlds top 20 environmental photography winners 2020 - Mohd Pirdaus Mat Husain; Mohd Nor Shahizan Ali; Ammar Redza Ahmad Rizal (Penerbit Universiti Kebangsaan Malaysia, 2024)
In today's digital era, photography has experienced a transformative shift, revolutionizing how we capture, share, and engage with images. Advancements in technology and the widespread availability of digital devices have made photography more accessible than ever. This has resulted in a proliferation of visual content across various platforms, shaping our visual culture and influencing societal perceptions. With the rise of social media and online platforms, photography has become a powerful tool for self-expression, storytelling, and documentation. Therefore, the main objective of this research is to identify the relationship between communication technology, image technicalities, and image narrative in documentary photographic images World Top 20 Environmental Photography Winner 2020 to audience awareness in the digital age. A quantitative approach (content analysis) was used to answer the study's objectives. The study data set was analyzed using IBM SPSS software version 27 to see whether there is a significant relationship. The study results found that the highest βeta value was the narrative image variable of 0.939, followed by the βeta value of the technical image of 0.035, and the last is the βeta value of the communication technology of 0.025. This suggests that image narrative variables are significantly related to interpreting documentary photo images of environmental issues that shape consciousness. The study's implications are anticipated to provide stakeholders insights into the critical elements of photography, serving as a guide for producing high-quality photographic images with meaningful content and effectively educating the public about environmental issues.